Collisionality dependence and ion species effects on heat transport in He and H plasma, and the role of ion scale turbulence in LHD. (1st August 2017) - Tanaka, K.; Nagaoka, K.; Murakami, S.; Takahashi, H.; Osakabe, M.; Yokoyama, M.; Seki, R.; Michael, C.A.; Yamaguchi, H.; Suzuki, C.; Shimizu, A.; Tokuzawa, T.; et al.
Abstract: Surveys of the ion and electron heat transports of neutral beam (NB) heating plasma were carried out by power balance analysis in He and H rich plasma at LHD. Collisionality was scanned by changing density and heating power. The characteristics of the transport vary depending on collisionality. In low collisionality, with low density and high heating power, an ion internal transport barrier (ITB) was formed. The ion heat conductivity ( χ i ) is lower than electron heat conductivity ( χ e ) in the core region at ρ < 0.7. On the other hand, in high collisionality, with high density and low heating power, χ i is higher than χ e across the entire range of plasma. These different confinement regimes are associated with different fluctuation characteristics. In ion ITB, fluctuation has a peak at ρ = 0.7, and in normal confinement, fluctuation has a peak at ρ = 1.0. The two confinement modes change gradually depending on the collisionality. Scans of concentration ratio between He and H were also performed. The ion confinement improvements were investigated using gyro-Bohm normalization, taking account of the effective mass and charge. The concentration ratio affected the normalized χ i only in the edge region ( ρ 1.0). This indicates ion species effects vary depending on collisionality. Turbulence was modulated by the fast ion loss instability. The modulation of turbulence is higher in H rich than in He rich plasma.